The cross-border effectiveness of mediated settlements and the Singapore Convention: great expectations? - Sánchez López, Bárbara (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper presents, with European and Spanish procedural perspectives, the problems posed by the harmonized framework for recognition and enforcement of settlement agreements proposed by the 2019 Singapore Convention. The automatic enforceability attached to the mere private document of mediated settlement that it is in writing, signed by the parties, resolving an international commercial dispute, calls into question the system of guarantees that after a long historical process has been established in many countries in the family of civil law to allow access to State enforcement proceedings.
Keywords: International mediated settlements; Mediation; Recognition and Enforcement; Commercial dispute resolution; Singapore Convention on Mediation; Enforceable instruments